Investigating the limestone quarries as geoheritage sites: Case of Mardin ancient quarry - Karataş Lale; Alptekin Aydın; Yakar Murat (Open Geosciences, 2023)
Abandoned quarries are valuable as a tourism element, as they exhibit the building material of the buildings built in the geographical area they are located in as historical objects. However, in order to determine how the quarries can be used for tourism purposes, it is necessary to determine the constraints on the choice of solution in spatial arrangements. The aim of this study is to investigate how the ancient limestone quarry of Mardin, which is a natural and cultural geological heritage, can be used for tourism and to develop suggestions. Within the scope of the study, in order to examine the possibilities of how an idle quarry located in Mardin province in Turkey can be used for tourism, the constraints in the selection of the post-use solution will be determined. In order to determine whether the Mardin quarry is accessible and safe to visit, various field studies were carried out in the study area, laboratory experiments and analyses. The caves were scanned with a 3D laser scanner, and its plans and sections were obtained. The findings were evaluated and suggestions were developed for the use of the ancient limestone quarry for tourism.